(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
The rapid expansion of digital communication technologies and social media platforms has transformed human interaction, communication, and social participation in unprecedented ways. While digital platforms have enhanced opportunities for expression, networking, education, and economic participation, they have simultaneously created new forms of cyber victimization and online abuse, particularly targeting women. Among the most disturbing forms of cybercrimes against women are cyber defamation and morphing of women’s images, which seriously threaten women’s dignity, privacy, reputation, and psychological well-being. Morphing refers to the digital manipulation or alteration of photographs to create obscene, sexually explicit, misleading, or defamatory content, which is often circulated through social media platforms, websites, messaging applications, and anonymous online forums. Cyber defamation, on the other hand, involves publication or transmission of false, malicious, or defamatory statements through electronic communication with the intention of damaging the reputation and social standing of individuals. In India, incidents involving morphing of women’s photographs, deepfake pornography, revenge-based circulation of altered images, and defamatory online campaigns have significantly increased due to rapid digitalization and social media penetration. Women frequently become victims of online exploitation through fake profiles, manipulated images, cyber stalking, online blackmail, and non-consensual publication of intimate content. Such offences create severe psychological trauma, reputational injury, emotional distress, social isolation, and professional consequences for victims. The anonymity and borderless nature of cyberspace make investigation and prosecution of such offences particularly challenging for law enforcement agencies. The present article critically examines the socio-legal dimensions of cyber defamation and morphing of women’s images in India. The study analyses constitutional protections, provisions of the Information Technology Act, 2000, Bharatiya Nyaya Sanhita, 2023, judicial interpretations, and enforcement mechanisms relating to online defamation and cyber exploitation of women. The article also explores technological challenges, evidentiary complexities, digital forensic issues, underreporting of offences, and emerging threats posed by artificial intelligence and deepfake technologies. Further, the study evaluates the role of cyber cells, intermediary liability, social media governance, and institutional mechanisms in protecting women from online victimization. The article concludes that although India has developed a growing legal framework to address cybercrimes against women, stronger enforcement, technological preparedness, legal reforms, digital awareness, and victim-centric approaches are necessary for ensuring meaningful cyber protection and safeguarding women’s dignity in the digital age.